The Discourse of Whole Class Teaching: A Comparative Study of Kenyan and Nigerian Primary English Lessons - Abd-Kadir, Jan; Hardman, Frank (Language and Education, 2007)
This paper explores the discourse of whole class teaching in Kenyan and Nigerian primary school English lessons. Twenty lessons were analysed using a system of discourse analysis focusing on the teacher-led three-part exchange sequence of Initiation – Response – Feedback (IRF). The focus of the analysis was on the first and third part of the IRF sequence as it is here that research suggests teachers can enhance pupil learning through questions and follow-up which asks pupils to expand on their thinking, justify or clarify their opinions, or make connections to their own experiences. The findings suggest that teacher questions were mainly closed requiring recall of information and teacher follow-up, where it occurred, often consisting of a low level evaluation of a pupil response, thereby severely constraining opportunities for pupil participation in the classroom discourse and higher order thinking. The implications of the findings are considered in the light of their impact on classroom pedagogy and the professional development of Kenyan and Nigerian primary teachers.